Cocirculação dos vírus Dengue e Zika durante a epidemia de Chikungunya no Estado do Ceará em 2017 - Silva, Debora Bezerra (2020)
In recent years, viruses such as dengue (DENV), Zika (ZIKV) and chikungunya (CHIKV) have produced a large number of epidemic outbreaks causing a significant increase in morbidity and mortality rates. Cocirculation between arboviruses is an additional challenge, not only for diagnosis and assistance to patients, but for epidemiological surveillance. The objective here was to conduct a seroepidemiological and molecular study of chikungunya in the state of Ceará during the epidemic season of 2017, identifying possible cases of codetection and / or coinfection of CHIKV with DENV and / or ZIKV. Through a cross-sectional study, 370 were selected from the biorepository at the Central Laboratory of Public Health of Ceará (LACEN-CE), consisting of samples referred for chikungunya diagnosis between April and September of 2017 that were reactive for IgM anti-CHIKV and that was up to 100 days of symptoms at the time of collection. These samples were aditionally tested by ELISA for IgG anti-CHIKV, both IgM and IgG anti-DENV and anti-ZIKV and NS1 antigen of dengue, as well as by molecular biology (qRT-PCR) for each CHIKV, DENV and ZIKV. Sociodemographic data were obtained from both epidemiological records and laboratory environment management system (GAL) and then compiled with laboratory results generated by this study for statistical analyses (Stata, v. 14.0). Of these 370 selected samples, 11 were excluded due to technical issues and 359 kept in the study. The results showed a predominance of females (64.9%), aged between 30-59.9 years (49.6%) with a median of 37.9 years. Samples with self-reported onset of symptoms between 6 and 10 days were the majority (76.9%), with a median of 6 days, and regarding the origin of the referral, the largest number of cases were from the city of Fortaleza (18 , 6%). Remarkably, in approximately 1 out of 4 samples examined (24.8%, 89/359) codetection of CHIK was observed with other studied arboviruses, the most frequent of which was between CHIKV / DENV (88.8%, 79/89), with statistical significance when compared to CHIKV / ZIKV (7.8%, 7/89). A triple detection (CHIKV / DENV / ZIKV) was demonstrated in 3.4% of that total (3/89). The frequency of IgG anti-CHIKV was 29.2%, IgG anti-DENV (82.6%) and IgG anti-ZIKV (49.3%); 59.4% had reactive serology for both (anti-DENV / ZIKV IgG). The NS1-DENV antigen was reactive in 1.76% of the samples, while the detection by qRT-PCR for CHIKV was confirmed in 53 of the 359 samples (14.8%), however there was no significant associations of these parameters with the time of symptoms reported. The results of this study confirmed that arboviral co-circulation during the chikungunya epidemic period in 2017 and revealed an elevated co-detection rate, particularly with DENV, in patients with a primary diagnosis of chikungunya. It also highlights the importance of undertaking complementary laboratory tests for establishing differential diagnosis in areas of endemic cocirculation of arboviruses, thus crucially contributing towards more effective surveillance measures to monitoring outbreaks.